Солдатлэн данэз: кылбуръёс но поэмаос / Николай Байтеряков - Байтеряков Николай Семенович (Удмуртия, 1987)
Экземпляры: (20240227) / Инвентарный номер: 17383 / Цена: 0.45 / Сис.шифр: С(удм) / Авт.знак: Б 18 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)^VLBC/RL